Using gonadotropin-releasing hormone agonist before frozen embryo transfer may improve ongoing pregnancy rates in hyperandrogenic polycystic ovary syndrome women. (2nd September 2017) - Tsai, Hsiao-Wen; Wang, Peng-Hui; Lin, Li-Te; Chen, San-Nung; Tsui, Kuan-Hao
Abstract: Polycystic ovary syndrome (PCOS), affecting more than 5–10% of woman at reproductive childbearing age, is characterized by anovulation and hyperandrogenism. Frozen-thawed embryo transfer (ET) has been widely used for PCOS women to minimize the risk of ovarian hyperstimulation syndrome. However, the hyperandrogenic status of PCOS women deteriorates endometrial function, which has subsequently increased miscarriage rates in PCOS women. Therefore, we conducted this retrospective study to compare the pregnancy outcomes of hyperandrogenic PCOS women with ( n  = 29) and without ( n  = 31, controls) pretreatment of gonadotropin-releasing hormone (GnRH) agonist before frozen-thawed ET. We found that pretreatment with GnRH agonist before frozen-thawed ETs could not significantly improve the clinical pregnancy rate in these hyperandrogenic PCOS women. However, the ongoing pregnancy rate was significantly increased in women with GnRH agonist pretreatment (odds ratio: 3.98, 95% confidence interval: 1.12–14.20, p  = 0.033). We concluded that androgen deprivation status due to pretreatment with GnRH agonist might improve the ongoing pregnancy rate in hyperandrogenic PCOS women. Additional large, well-designed prospective studies are worthwhile and necessary.